Bacterial Community Structure in Sago Pith and Sago Waste Water and Its Potential Uses as Organic Acids Producer: Bacterial community structure in sago - Eka Pratiwi Tenriawaru; Suharjono Suharjono; Tri Ardyati; Elok Zubaidah (Journal of Tropical Life Science, 2022)
Sago is one of commodities in South Sulawesi. The extraction process of sago flour produces waste water that still contains organic matter and smells sour. So, it has the potential as a pollutant. The sour odor produced allows the presence of acid-producing bacteria that can be used for waste treatment. The objective of this research is to explore the bacterial community structure in sago pith and sago waste water through high-throughput sequencing technology and its potential uses as organic acids producer. Samples were obtained from a traditional sago factory in Palopo City, South Sulawesi, Indonesia. The acidity degree, total dissolve solid, and temperature were measured in the sago pool at the sampling area, while the nutrient contents were analyzed by titration method in Testing Laboratory of Food Quality and Food Safety, Brawijaya University. Bacterial cells in the sago waste water were acquired through a multilevel filtering process on filter paper with pore nitrocellulose membrane sizes of 0.45 and 0.20 Âµm. Total DNA trapped in the nitrocellulose membrane with pore size of 0.20 Âµm was isolated using FastDNA Spin Kit (MPBIO) and the V3-V4 regions of 16S rDNA (341f-806r) were amplified. Amplicons were analyzed by Miseq of Illumina and further analyzed by Muscle v.3.8.31, QIIME v.1.7.0, and R v.2.15.3. The result shows that nutrient content in sago pith is higher than in sago waste water. Both samples are dominated by Phylum Proteobacteria and share 189 common bacterial species. The dominant bacteria that can produce organic acid in sago pith are Dysgonomonas sp., Propionispira sp., and Lactobacillus pentosus. While, Lactobacillus mali and Gluconobacter frateurii are the dominant organic acid-producer bacteria in sago waste water. Â Keywords: Bacterial community structure, Next generating sequencing, Sago pith, Sago wastewater